Atypical de Quervain's thyroiditis diagnosed as atypia of undetermined significance by cytology and suspicious for cancer by Afirma Genomic Sequencing Classifier. Issue 8 (3rd March 2021) - Yu, Run; Yang, Sung‐Eun; Rao, Jianyu
Abstract: We report a case of atypical de Quervain's thyroiditis diagnosed as atypia of undetermined significance by cytology and suspicious for cancer by Afirma Genomic Sequencing Classifier. A 71‐year‐old male underwent thyroid ultrasound for goiter and was found to have two American Thyroid Association (ATA) 2015 high‐suspicion nodules. The larger, 2.2‐cm nodule was biopsied and the cytology showed atypical follicular cells and histiocytes. The Afirma Genomic Sequencing Classifier (detecting mRNA expression profile) result was ''suspicious'' (risk of malignancy 50%) but Afirma Xpression Atlas (detecting specific mutations) did not find mutations in BRAF V600E, RET/PTC1, or RET/PTC3. The patient saw two endocrine surgeons and two endocrinologists who each recommended hemithyroidectomy. The patient chose to monitor the nodules. A new diagnostic ultrasound performed 3 months after the first one showed that the thyroid was significantly smaller and the previously seen nodules were no longer found. Re‐examination of the cellular smears confirmed that the cytological findings were also compatible with de Quervain's thyroiditis. This case illustrates that atypical de Quervain's thyroiditis should be in the differential diagnosis of thyroid nodules for cytologists, radiologists, and clinicians. Furthermore, this case demonstrates that atypical de Quervain's thyroiditis can generate false positive results of molecular tests for indeterminate thyroid nodules.